The roles of Employees Provident Fund in the 21st century / Low Kuek Long (Universiti Teknologi MARA, Sarawak, 1996)
Employees Provident Fund (EPF) was established in 1951 under the Employees Provident Fund Act. The EPF savings are primarily meant for life after retirement. The combined contributions from the employees themselves and their respective employers provide a cushion of comfort to enable contributors to maintain their lifestyle after retirement. So far, EPF has accumulated assets of about 98.9 billion. However, with the one per cent increase in contribution from both the employees and employers, this figure will balloon and may easily reach the RM100 billion level well before the turn of the century. As the funds continue to swell, the roles of EPF have to change with changing times to meet the changing needs of its contributors in the 21st century.